Elastic scattering studies of aligned DMPC multilayers on different hydrations 1. Issue 5 (2010) - Trapp Trapp, Marcus Marcus; Juranyi Juranyi, Fanni Fanni; Tehei Tehei, Moeava Moeava; van Eijck van Eijck, Lambert Lambert; Demé Demé, Bruno Bruno; Gutberlet Gutberlet, Thomas Thomas; Peters Peters, Judith Judith
Abstract : Biological membranes, consisting mainly of phospholipids and proteins, are organized in a bilayered structure which exhibits dynamical behaviour within time regimes ranging from 10 –12 s with the motion of alkyl chain defects and 1 s corresponding to collective excitations of the bilayer [ Europhysics Letters 8 (1989), 201–206]. With the prominent role hydration plays on the structural phase behaviour of phospholipids membranes, it is essential for a better description of membranes to understand also the influence of hydration on the dynamics of membrane systems. In the present study we have performed neutron scattering investigations on highly oriented DMPC-d54 multilayers at two different relative humidity (rh) levels. Our results reveal the strong influence of hydration on the local membrane dynamics, i.e., head group dynamics.